Pengaruh Efikasi Diri, Kemampuan Literasi Digital, Keahlian Manajemen, dan Soft Skill Terhadap Kesiapan Kerja Mahasiswa Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Riau - Deswarta; Hendra Eka Saputra; Fito Albajili (ITB AAS Indonesia Surakarta, 2026)
This study aims to examine and analyze the effects of self-efficacy, digital literacy skills, management skills, and soft skills on the work readiness of management students at the Faculty of Economics and Business, Universitas Islam Riau. The population of this study consists of all management students at the Faculty of Economics and Business, Universitas Islam Riau. A sample of 90 students was determined using the Slovin formula with a purposive sampling technique. Data were collected through questionnaires and interviews. The results indicate that self-efficacy, digital literacy skills, managerial skills, and soft skills have a significant effect on the work readiness of management students at the Faculty of Economics and Business, Universitas Islam Riau.